Including carbon taxation risk in Deutsche Bundesbank's in-house credit assessment system (ICAS): An empirical analysis - Justus Grundmann; Anna Silberbach; Laura Auria (Deutsche Bundesbank, 2023)
Carbon taxation is currently one of the most salient risks with respect to the transition to a low carbon economy for European enterprises. Although there are ample scientific studies that analyse the economic effect on a macro scale (climate stress tests etc.), there is not much literature to be found at a granular level. The present exercise aims at analysing the potential financial risks resulting from a carbon intensive production conveyed through an increased tax burden. It is based on the idea of scenario analysis and uses the European Emissions Trading System (EU ETS) as a data source. The EU ETS also serves in a broader sense as a stance for the institutional framework that is assumed in the exercise. The developed model delivers a stressed probability of default estimated at the company level on the basis of the individual financial ratios. It can serve as a tool in different ways: It can up-date the rating relevant balance sheet information to a more current state and is thus helpful in the operative rating business, when political and economic developments are dynamic or include turning-points. It can be extended beyond the EU ETS data to explore hypothetical scenarios and long term prospects, too. Carbon intensive production will very likely be in the focus of transition enforcing policy measures in the coming years. The respective enterprises will most likely be required to change their business and/or production model. So the outcome of adverse hypothetical scenarios can be interpreted as measure of the structural pressure to adapt and its impact on the creditworthiness of the company. The paper will outline the developed methodology and present some results for German enterprises.
Keywords: E50; E58; 330; carbon taxation risk; climate change risk; transition risk; (in-house) credit assessment; scenario analysis; EU ETS